2001
DOI: 10.1248/cpb.49.1299
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Behavior of Eukaryotic Initiation Factor 4E in Supramolecular Formation with 4E-Binding Protein 1 and mRNA Cap Analogue, Studied by Spectroscopic Methods.

Abstract: GpppA/G-bound eIF4E to an irregular structure, although such a structural change was not observed for eIF4E alone. The association constant of 4EBP1 with m 7 GTP-or m 7 GpppA/G-bound eIF4E was by two orders of magnitude larger than that with eIF4E alone. These results suggest the close interrelation in the supramolecular formation of 4EBP-eIF4E-mRNA cap structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Human eIF4E contains eight tryptophanes, making it a strongly fluorescent protein. This property has been exploited in previous studies (44)(45)(46). We observed that the 4EGI1[E/Z] analogs also induce quenching of the protein intrinsic fluorescence.…”
Section: Mutations and Fluorescence Polarization Experiments A Humanmentioning
confidence: 74%
“…Human eIF4E contains eight tryptophanes, making it a strongly fluorescent protein. This property has been exploited in previous studies (44)(45)(46). We observed that the 4EGI1[E/Z] analogs also induce quenching of the protein intrinsic fluorescence.…”
Section: Mutations and Fluorescence Polarization Experiments A Humanmentioning
confidence: 74%
“…It is interesting to note that both of these studies evaluate the capacity of in vitro phosphorylation at Thr46 to disrupt pre-existing 4E-BP1:eIF4E complexes and utilize cap column purification to isolate eIF4E-bound 4E-BP1. This experimental detail is particularly relevant, as it has been shown that the RNA cap can exert an allosteric effect stabilizing 4E-BP1:eIF4E binding 14, 36 . Taken together, our data and these previous reports could suggest that Thr46 phosphorylation is sufficient to block the initial binding between eIF4E and 4E-BP1 as observed by far western analyses, but that hyperphosphorylation of 4E-BP1, including at Ser65, is required to disrupt existing 4E-BP1:eIF4E complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The excitation wavelength was set at 280 nm and the emission spectra were measured between 300 and 400 nm. RXRαLBD protein was incubated with different concentrations of the test compound at 4°C for 1 h. The dissociation equilibrium constant (K D ) of the test compound binding to RXRαLBD protein was fitted by the previously reported method (Shen et al, 2001).…”
Section: Fluorescence Quenching Assaymentioning
confidence: 99%